STRATEGI GURU MENGAJAR AQIDAH (NILAI KEJUJURAN) DENGAN METODE STORYTELLING DI SD AL-ALIF CIKARANG - Maghfira, Amila; Basuki, Danang Dwi (MIDA : Jurnal Pendidikan Dasar Islam, 2025)
Instilling the value of honesty from an early age is a crucial aspect of character education, particularly in Aqidah learning at the elementary school level. This study aims to explore teacher strategies in instilling the value of honesty through the storytelling method for lower-grade students at SD Al-Alif Cikarang. Using a descriptive qualitative approach, data were collected through in-depth interviews with an Aqidah teacher and analyzed through data reduction, data display, and conclusion drawing. The findings indicate that teachers implement structured strategies including relevant story selection, interactive delivery, reflective discussions, and behavioral reinforcement. The stories used include those of the Prophets, Companions, and relatable daily experiences, presented through emotional narration, interactive dialogue, and visual media. Students responded with high enthusiasm and active participation, showing significant behavioral changes related to honesty. Despite challenges such as limited media and teacher storytelling skills, solutions such as teacher training, digital media integration, and collaboration with parents proved effective. This study affirms that storytelling is an effective strategy for internalizing the value of honesty and strengthening character education in primary schools.